2014
DOI: 10.1111/apa.12785
|View full text |Cite
|
Sign up to set email alerts
|

Stable prevalence of obesity in Swedish schoolchildren from 2008 to 2013 but widening socio‐economic gap in girls

Abstract: The overall prevalence of overweight and obesity was stable over 5 years, but we detected growing inequality in obesity and increasing prevalence of thinness in girls. With these regionally representative data, we can draw conclusions about West Sweden, despite an absence of continued national surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 22 publications
5
37
3
Order By: Relevance
“…In contrast to the increasing prevalence of weight problems among the boys in our study cohort, a study of randomly selected Swedish youths reported that 17% were overweight, including 3% who were obese (5), and another study reported that the obesity epidemic in Sweden had levelled off (28). The prevalence in fifth-grade boys rose from 25.5% to 30%, but fifth-grade girls decreased from 21.8% to 16.7%.…”
Section: Discussioncontrasting
confidence: 74%
“…In contrast to the increasing prevalence of weight problems among the boys in our study cohort, a study of randomly selected Swedish youths reported that 17% were overweight, including 3% who were obese (5), and another study reported that the obesity epidemic in Sweden had levelled off (28). The prevalence in fifth-grade boys rose from 25.5% to 30%, but fifth-grade girls decreased from 21.8% to 16.7%.…”
Section: Discussioncontrasting
confidence: 74%
“…This favorable finding may be partly the result of the legislative measures introduced in Hungary in the last few years (table 4). Childhood obesity has apparently plateaued in some COSI countries (e.g., in Sweden or Spain) or even decreased in others (e.g., in Italy or Ireland) [26]. However, trends in subgroups may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, trends in the number of children who are overweight or obese have been increasing since the 1970s and Sweden is no exception. 3 Although there has been some Swedish reports indicating that the prevalence is leveling off or stable in children, 4,5 in the past 30 years the number of overweight children has doubled. 6 As a combination of low PA and large amounts of SB are related to overweight and obesity, 7 the compilation of this data are vital for policy makers, researchers, and various stakeholders to assess problem areas and intervene in appropriate ways.…”
mentioning
confidence: 99%